(untitled) (Global Journal of Management and Business Research, 2022)
Financial reporting to external third parties is the primary document based on which at least in theory a company s creditworthiness should be assessed Income capital financial and sustainability performance should be understood through a thorough analysis of the financial reporting and sustainability report data Here we will focus exclusively on Financial reporting As we will see Financial reporting intended for the outside world is characterised by an information gap that tends to preserve the company s right to information and privacy